Role of acceptor strength on OFET properties of small molecular organic semiconducting materials with D-A-D architecture - Sasikumar, M.; Bharath, D.; Kumar, G. Siva; Chereddy, Narendra Reddy; Chithiravel, S.; Krishnamoorthy, K.; Shanigaram, Balaiah; Bhanuprakash, K.; Rao, V. Jayathirtha (Synthetic Metals, 2016)
Two organic semiconducting materials 2,5-didodecyl-3,6-bis(4-(11-dodecyl-11H-benzo[a]carbazol-8yl)phenyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione. (BCDPP) and 1,5-didodecyl-3,7-bis(4-(11-dodecyl-11H-benzo[a]carbazol-8-yl)phenyl)dipyrrolo[3,2-b:3',2'-e]pyrazine-2,6(1H,5H)-dione (BCPzDP) with D-A-D architecture have been designed, synthesized and well characterized. Both the materials have benzocarbazole donor end-capping units. While BCDPP contains well explored diketopyrrolopyrrole (DPP), BCPzDP possesses electron deficient dipyrrolopyrazinedione (PzDP) as acceptor moiety. The importance of the nature of acceptor moiety in tuning the charge transport properties of the synthesized materials is explored. Thermal, photo-physical and electrochemical properties of these materials are measured and solution processed OFETs are fabricated. OFETs with BCDPP show unipolar p-type semiconducting properties with hole mobility of 1.02 x 10(-4) cm(2) V-1 s(-1) and OFETs of BCPzDP exhibit ambipolar charge transport behaviour with optimal saturation hole and electron mobilities of 0.0054 and 0.0013 cm(2) V-1 s(-1), respectively. (C) 2016 Elsevier B.V. All rights reserved.

Liquid crystalline supramolecular crosslinked polymer complexes of ditopic rylenebisimides and P4VP - Saibal, B.; Narayan, Rekha; Chithiravel, S.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Perylenebisimide and naphthalenebisimide (PBIPDP and NBI-PDP) end functionalized with pentadecyl phenol is designed as ditopic hydrogen bonding acceptors to form supramolecular crosslinked network with poly(4-vinyl pyridine) (P4VP). The pristine PBI-PDP has been grown as single crystals from DCM-MeOH (dichloromethane-methanol) mixture at room temperature, which revealed a P21 space group. Noticeably, the pentadecyl alkyl chain shields the aromatic perylene core on both sides resulting in the absence of p-p interaction in single-crystal assembly. The naphthalenebisimide derivative exhibits thermotropic liquid crystalline behavior, while both the molecules exhibits lyotropic liquid crystalline phases in tetrahydrofuran (THF), which were characterized using a combination of differential scanning calorimeter, X-ray diffraction, and polarized light microscopy. The hydrogen-bonded complex of both the rylenebisimides with P4VP preserves the mesomorphic properties in THF. The electron transport mobility measured by space charge limited current measurements reveals a two orders of magnitude increase in the charge transport in the P4VP complex compared to that of the pristine molecule. The average electron mobility obtained is mu(e, avg): 10(-3) cm(2)/Vs for P4VP-PBI compared to mu(e, avg): 10(-5) cm(2)/Vs for pristine PBI derivative. (C) 2017 Wiley Periodicals, Inc.
Keywords: crystal structures; ditopic rylenebisimide; hydrogen bonding; lyotropic liquid crystal; P4VP; Self-assembly; supramolecular crosslink; supramolecular structures